2012
DOI: 10.1038/jhh.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training on biomarkers of vascular function and oxidative stress in young African-American and Caucasian men

Abstract: African Americans (AA) have an earlier onset of hypertension and a different vascular profile than their Caucasian (Cau) peers. Research suggests that biological mediators of vascular inflammation are different among these groups in hypertensive populations. Resistance training (RT) is an important exercise modality which improves the vascular profile of young AA men. We examined the role of RT on biomarkers of vascular function and oxidative stress in BMI-matched AA and Cau men. Six weeks of RT elicited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
2
25
0
2
Order By: Relevance
“…It has been reported that resistance training appears to prevent metabolic disorders such as dyslipidemia, impaired fasting glucose, pre-hypertension, and increased waist circumference, but not hypertension 37 , while recognizing that increased strength may improve vascular health and reduce complications 38 and mortality among hypertensive individuals 39 . The statistical association between handgrip strength and hypertension may mean that muscle strength expresses overall individual fitness 40 more than a direct relationship with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that resistance training appears to prevent metabolic disorders such as dyslipidemia, impaired fasting glucose, pre-hypertension, and increased waist circumference, but not hypertension 37 , while recognizing that increased strength may improve vascular health and reduce complications 38 and mortality among hypertensive individuals 39 . The statistical association between handgrip strength and hypertension may mean that muscle strength expresses overall individual fitness 40 more than a direct relationship with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have linked exercise to reductions in MMP-9 levels, but have been limited to resistance training programmes in men only or exerciseplus-diet interventions in men with metabolic syndrome and children with atherosclerotic risk factors [24][25][26]. Similarly, Kadaglou et al demonstrated that in a diabetic population, a 16-week exercise programme resulted in decreased plasma levels of MMP-9 [27].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental models of hypertension and in patients with coronary artery disease, exercise reduced vascular Nox activity and ROS production, ameliorated vascular injury, and reduced blood pressure (1). Resistance training in men decreased circulating levels of matrix metalloprotease-9 and 8-isoprostane (43). However, in elderly patients, combining antioxidant therapy with exercise negated blood pressure-lowering beneficial effects of exercise (43).…”
mentioning
confidence: 97%
“…Resistance training in men decreased circulating levels of matrix metalloprotease-9 and 8-isoprostane (43). However, in elderly patients, combining antioxidant therapy with exercise negated blood pressure-lowering beneficial effects of exercise (43).…”
mentioning
confidence: 97%